Fluktuasi Nilai IHSG: Dampak Kondisi Inflasi Tahun 2023 di Indonesia - Jufri Yandes; Destiana Destiana; Ridha Azka Raga; Jasrial Jasrial; Aji Fajar Suryo Antoro; Husna Putri Pertiwi (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
In navigating the flow of life, investment becomes the main pillar to ensure financial sustainability in the future. This study explores the possible influence of inflation condition in 2023 on the fluctuation of JCI value from January to December. Time series data of JCI for 12 months is used from Yahoo Finance source, and linear regression analysis through EViews is used to test the hypothesis with t-test, and data from Bank Indonesia for inflation condition. The interesting result of the study states that the fluctuation of JCI cannot be influenced by the inflation condition in 2023, especially in the studied time frame. This suggests that other factors may be more dominant in determining the movement of the JCI during that period. The importance of this study is not only to understand the dynamics of the capital market, but also as a guide for investors in making more targeted investment decisions. However, this study is not free from limitations, such as the limited time data available and the generalisation of results only to a certain time span. Hopefully, future research will identify and correct these limitations to gain a more comprehensive understanding of the relationship between economic conditions particularly regarding inflation, JCI, and the capital market. Thus, investors in the future can face changes in economic conditions more confidently and strategically.